UPAYA PENINGKATAN KESADARAN MASYARAKAT TEBET JAKARTA SELATAN DALAM MELINDUNGI HUTAN INDONESIA - Achmad Ismail; IGA Raka Putra Satwika; Tri Rumayanto (RAMBIDEUN : Jurnal Pengabdian Kepada Masyarakat, 2023)
Increasing air pollution is one of the main problems of international concern considering the negative impact on the survival of living creatures in the world. For example, the impact on human health, the economy, and even the environmental ecosystem. Various plants, generally forests in Indonesia, have an important role in reducing air pollution. Therefore, the team implementing community service activities considered it important to build awareness among the community, especially in the environment of RT 07/RW 02 of West Tebet, Tebet, South Jakarta, DKI Jakarta. The method for implementing community service activities was in the form of online socialization with 4 strategies that can be carried out by the community, namely campaigns, legal advocacy, research for publication, and partnership collaboration with stakeholders. The results of the implementation of activities showed an increase in awareness of community service targets, especially youth, to care for trees, plants and the surrounding environment as an effort to protect Indonesia's forests. This can be seen from the discussion or question and answer sessions held during the community service activities.